Impact of COVID-19 on the finance sources of women in the agricultural sector: the case of Kosovo - Jehona Shkodra; Verlinda Bajrami (Cogent Economics & Finance)
The aim of this study is to analyse the level and determinants of women farmers’ access to financial resources in agriculture in Kosovo. The study describes the socio-economic characteristics of women farmers and identifies the socio-economic factors that influence access to financial resources. Primary data were collected from one hundred forty-six (146) women farmers who had access to a source of finance using multistage random sampling. Data were analysed using descriptive statistics, Likert scores, and probit regression estimates. 61.94% of the women had a farm size between 0.2 and 1.0 hectares and had an average farming experience of 8.33 years. The majority, 40.48% of the respondents, had formal education. They had a relatively high number of sources of finance through “family savings” and did not have access to finance through “borrowing from family members”. The probit regression estimation showed that education level, gross annual income, and net worth each exerted a significant positive influence on the probability. This implies that the relevant institutions in the country should develop policies and programmes for women farmers with low levels of education, income, and net worth.